Impacts of blood feud in Amhara National Regional State, Ethiopia. Issue 1 (2nd January 2023) - Alamineh, Gubaye Assaye; Dires Dinberu, Abebe; Ali, Mohammed Seid; Anteneh, Kumilachew Siferaw
ABSTRACT: This article discusses the major impacts of blood feud in Amhara National Regional State (ANRS), northern Ethiopia. In-depth interviews, focus group discussions and document analysis were used to generate data. The findings revealed that blood feud has both positive and negative impacts. The positive impact is its role in promoting and strengthening unity within the relatives of counterparts. Moreover, blood feud serves as an instrument of deterrence for further killings and acts of revenges. On the same token, it facilitates family integration and cohesion of the feuding parties to ensure a common security defense. However, blood feud costs human lives in addition to its huge psychological and financial externalities upon concerned parties. It has also been resulting in family disintegrations, migration and social vulnerabilities of groups in the study areas.